Modeling of Petrochemical industries wastewater COD Removal with DOE&ANN - ali Haghighi Asl; amin ahmadpour; narges fallah (مجله مدل سازی در مهندسی, 2018)
In this research, photocatalytic degradation method for COD(CHEMICAL OXYGEN DEMAND Value) removal has been introduced to treatment of petrochemical industries wastewater as an adaptable method and effective parameters in the process performance have been investigated. Therewith, by using commercial photocatalyst of titanium dioxide and empirical measurement of COD parameter, decrease percentage of this parameter of photocatalytic process during 90 minutes investigated via DOE&ANN method. To carry out experiments,A photocatalytic reactor with agitator used which UV-C lamps submerged within photocatalyst solution in the wastewater sample. Results of experiments at optimized conditions indicated that two models is in a good agreement with the consequences. These results demonstrated that photocatalyst concentration increase in the neutral pH state to optimized amount of 0.84 grams per liter under unlimited conditions and 2 grams per liter under limited conditions, causes removal increase of COD to 93 and 77 percent, respectively(from 180 to 90 and 294 respectively).